Construcciones con ‘ser focalizador’ en narcotelenovelas colombianas: de Antioquia al Valle del Cauca - Diez del Corral Areta, Elena (2018)
This paper offers new data on the dialectal variation of focalizing ser (‘to be’) constructions, through the study of two Colombian soap operas, whose action is located in the departments of Antioquia and Cauca’s valley. The comparative analysis of these two dialectal zones highlights the vitality of this construction, which is spreading through areas in which it has not been recorded until now. Also, from a formal perspective, this study shows the syntactic flexibility of the structure, in which we frequently find interpolations, other elements that emphasize such as pero and even double focalizations.